1960
DOI: 10.1149/1.2427522
|View full text |Cite
|
Sign up to set email alerts
|

Fused Salt Polarography Using a Dropping Bismuth Cathode

Abstract: An apparatus is described which is suitable to study fused chlorides by the polarographic technique. Dropping bismuth is used in a way analogous to dropping mercury. Polarographic waves are shown for PbCl2 , ZnCl2 , and CdCl2 in a normalLiCl‐normalKCl eutectic melt at 450°C. The method serves as an analytical tool at high temperatures, besides yielding physicochemical information such as diffusion coefficients by application of the Ilkovic equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

1961
1961
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 1 publication
2
18
1
Order By: Relevance
“…In general, the diffusion coefficients determined in the present studies are somewhat lower than the previously reported literature values for Ni(II) (22), Co(II) (44), Cd(II) (22,(43)(44)(45)(46), and Pb(II) (22,44,46). However, there is a good agreement between our value for the diffusion coefficient of Co(II) and the value reported by Naryshkin et al (22) and between our value for the diffusion coefficient of Pb(II) and the value found by Thalmayer, Bruckenstein, and Gruen (45).…”
Section: Ep--ep~contrasting
confidence: 86%
“…In general, the diffusion coefficients determined in the present studies are somewhat lower than the previously reported literature values for Ni(II) (22), Co(II) (44), Cd(II) (22,(43)(44)(45)(46), and Pb(II) (22,44,46). However, there is a good agreement between our value for the diffusion coefficient of Co(II) and the value reported by Naryshkin et al (22) and between our value for the diffusion coefficient of Pb(II) and the value found by Thalmayer, Bruckenstein, and Gruen (45).…”
Section: Ep--ep~contrasting
confidence: 86%
“…These values are in good agreement with the literature data. 3,9 The obtained results confirm that the reduction of Pb 2+ ions on the Mo substrate in the LiCl-KCl-PbCl 2 melt over the temperature range of 723-823 K is a one-stage diffusion-controlled reaction. …”
Section: Resultssupporting
confidence: 66%
“…Dependence of i d on the molar fraction of PbCl 2 and PbO difference in a LiCl-KCl-PbCl 2 -PbO melt at 773 K. complex compound: N Pb 2 OCl 2 = N PbO [9] The concentration of electroactive Pb 2+ particles that participate in the electrode process is equal to: [10] where N 0 PbCl2 -the initial molar fraction of PbCl 2 . The molar fraction was then recalculated to the molar concentration according to the equation:…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that further measurements, involving other metals, would be useful, and since this work was completed there have been further reports (18,19) of the successful use of liquid electrodes in melts. It is hoped that these electrodes will be used to extend the range of capacity data in molten salt systems and to confirm the tentative values shown in Fig.…”
Section: Ir~teryacial Capacitiesmentioning
confidence: 95%